Two souls, two thoughts, two self-schemas double consciousness can have positive academic consequences for African American. [article]. - Brannon, Tiffany N.; Markus, Hazel Rose; Taylor, Valerie Jones
African American can experience a double consciousness-the two-ness of being an American and an African American. The present research hypothesized that: (a) double consciousness can function as 2 self-schemas-an independent self-schema tied to mainstream American culture and an interdependent self-schema tied to African American culture, and (b) U.S. educational settings can leverage an interdependent self-schema associated with African American culture through inclusive multicultural practices to facilitate positive academic consequences. First, a pilot experiment and Studies 1 and 2 provided evidence that double consciousness can be conceptualized as 2 self-schemas. That is, African American culture. Then, Studies 3 and 4 demonstrated that incorporating African American culture within a university setting enhanced African Americans? persistence on academic relevant tasks. Finally, using the Gates Millennium Scholars dataset (Cohort 1), Study 5 conceptually replicated Studies 3 and 4 and provided support for one process that underlies the observed positive academic consequences. Specifically, Study 5 provided evidence that engagement with African American culture (e.g., involvement with cultural events/groups) on college campuses makes an interdependent self-schema more salient that increases African American students? sense of academic fit and identification, and, in turn, enhances academic performance (self-reported grades) and persistence (advanced degree enrollment in a long-term follow-up). The discussion examined double consciousness as a basic psychological phenomenon and suggests the intra- and intergroup benefits of inclusive multicultural settings. - - (from the authors)